Ecopreneurship Berbasis Photovoice untuk Menggali Potensi Wirausaha Generasi Z - Ni Wayan Ekayanti; Dewa Ayu Puspawati (Universitas Sebelas Maret, 2021)
Currently, environmental-based approaches are being encouraged, especially for entrepreneurial activities. Ecopreneurship is one of the efforts to carry out entrepreneurial activities that are concerned with environmental aspects, and not only concerned with profit. This ecopreneurship potential can be explored using photovoice, which is a learning medium through photographic techniques that have visual messages and narratives for the effectiveness of the meaning of the photo. The purpose of this study is to explore the potential of Generation Z Ecopreneurship through a photovoice approach. This study uses a photovoice-based community-based design (FGD), which was conducted from November 2020 to January 2021 in Canggu, North Kuta, with a generation Z community of 8 high school students. Data was collected using semi-structured interviews, WhatsApp, recorder and logbook, then the data was analyzed by using descriptive. The results of this study showed that in FGD 1 the themes were dominated by ecology, economy, efficiency and effectiveness, while in FGD 2 the themes that emerged were ecology, economy, efficiency and social. This shows that there is a change in the perception of the emergence of ecological and social themes from FGD 1 to FGD 2, which means that the community's perspective has been more open after planting the concept related to Ecopreneurship. So it can be concluded that photovoice can be used to explore the potential of Generation Z Ecopreneurship.